On Random Population Growth Punctuated by Geometric Catastrophic Events (Contemporary Mathematics, 2020)
Catastrophe Markov chain population models have received a lot of attention in the recent past. Besides systematic random immigration events promoting growth, we study a particular case of populations simultaneously subject to the effect of geometric catastrophes that causes recurrent mass removal. We describe the subtle balance between the two such contradictory effects.
Keywords: Markov chain, random population growth, geometric catastrophic events, recurrence/transience transition, height and length of excursions, extinction events, time to extinction, large deviations